Comparative Genomics of Prunus-Associated Members of the Pseudomonas syringae Species Complex Reveals Traits Supporting Co-evolution and Host Adaptation - Ruinelli, Michela; Blom, Jochen; Smits, Theo H. M.; Pothier, Joël F. (Frontiers in Microbiology, 2022)
Members of the Pseudomonas syringae species complex cause symptoms that are ranging from leaf spots to cankers on a multitude of plant species, including some of the genus Prunus. To date, a total of two species of the P. syringae species complex and six different pathovars have been associated with diseases on Prunus spp. which were shown to belong to different phylogenetic units (phylogroups) based on sequence similarity of housekeeping genes or whole genomes, suggesting that virulence to Prunus spp. may be the result of convergent pathoadaptation. In this study, a comparative genomics approach was used to determine genes significantly associated with strains isolated from Prunus spp. across a phylogeny of 97 strains belonging to the P. syringae species complex. Our study revealed the presence of a set of orthologous proteins which were significantly associated with strains isolated from Prunus spp. than in strains isolated from other hosts or from non-agricultural environments. Among them, the type III effector HopAY, predicted to encode for a C58 cysteine protease was found to be highly associated with strains isolated from Prunus spp. and revealed patterns supporting co-evolution and host adaptation.